Circular RNAs: Novel Regulators of Neuronal Development - van Rossum, Daniëlle; Verheijen, Bert M.; Pasterkamp, R. Jeroen (Frontiers in Molecular Neuroscience, 2016)
Circular RNAs (circRNAs) are highly stable, circularized long non-coding RNAs (lncRNAs). circRNAs are conserved across species and appear to be specifically enriched in the nervous system. Recent studies show that many circRNAs are expressed in a tissue- and developmental-stage-specific manner, reveal a striking (up)regulation of circRNAs during neuronal development, and detect their presence at synaptic sites. The exact functions of circRNAs remain poorly understood, but evidence from analysis of some circRNA molecules suggests that they could substantially contribute to the regulation of gene expression, particularly in architecturally complex and polarized cells such as neurons. Emerging evidence also indicates that circRNAs are involved in the development and progression of various neurological disorders. In this review, we summarize the molecular characteristics of circRNAs and discuss their proposed functions and mechanism-of-action in developing neurons.